Distributed source localization in wireless sensor networks - Meng, Wei (2013)
With the advent of low-cost, low-power wireless sensing devices, wireless sensor networks (WSNs) have found potential applications in environment monitoring, battle field surveillance, manufacturing and logistics, healthcare, etc. WSNs have been receiving increasing attention in recent years from researchers and practitioners. Source localization using measurements from spatially distributed sensors is an important application of WSNs. Many challenges arise when sensors are networked wirelessly due to the limited resources inherent to a sensor network. The main contribution of this thesis is to provide sensor resource management strategies and develop algorithms and protocols for distributed source localization and tracking in WSNs. Several types of sensor measurements are considered in this thesis, e.g., received signal strength (RSS), range, direction-of-arrival (DOA)/angle-of-arrival (AOA), time-of-arrival (TOA), time-difference-of-arrival (TDOA), etc.